Identification and characterization of the glutamine synthetase gene family in oat (Avena sativa L.) and the role of AsGS2-2C under drought stress - Yang, Mei; Zheng, Shanshui; Li, Jingya; Tong, Shilun; Zhang, Mingzhi; Cui, Guowen; Che, Chenghao; Zhang, Wenwen; Wang, Yaqian; Zhang, Taiming; Teng, Jian; Li, Bing; et al. (Frontiers in Plant Science, 2025)
Drought is a critical limiting factor for crop yield, posing a substantial threat to global food security and negatively influencing plant growth and development. As a crop used as both a grain and forage, the yield of oat (Avena sativa) is significantly affected by drought. Glutamine synthetase (GS) is a crucial enzyme in plant nitrogen metabolism and plays an essential role in nitrogen utilization, growth regulation, and yield formation. We used bioinformatics analysis to identify the GS gene family in oats, and employed molecular biology, genetics and plant physiology methods to investigate the drought-resistant function of AsGS2-2C. In this study, 11 oat AsGS genes were identified, and the gene family and expression patterns were analyzed. Our findings revealed that a majority of AsGS genes were upregulated under drought and salt stress, whereas they were downregulated in response to cold stress and abscisic acid treatment. Cloning and functional analysis of the AsGS2-2C gene revealed that transgenic tobacco overexpressing AsGS2-2C presented increased tolerance to drought stress in phenotype. Physiological analyses revealed an increase in antioxidant enzyme activities and a reduction in membrane damage in AsGS2-2C-overexpressing plants. Under drought conditions, the expression of stress-responsive genes (Cu/Zn-SOD, MnSOD, CBL1, GR1, GAPC, Gln1-5, and BI-1) was significantly elevated in AsGS2-2C transgenic tobacco. Interestingly, ACR11, GLU, ERD10B, Hxk3 and Ltp1 exhibited initial upregulation followed by subsequent downregulation. These findings provide valuable insights into the molecular mechanisms underlying drought tolerance mediated by AsGS2-2C in oat, offering potential targets for crop improvement against drought.